Communication and ethical considerations for fertility preservation for patients with childhood, adolescent, and young adult cancer: recommendations from the PanCareLIFE Consortium and the International Late Effects of Childhood Cancer Guideline Harmonization Group. Issue 2 (February 2021) - Mulder, Renée L; Font-Gonzalez, Anna; van Dulmen-den Broeder, Eline; Quinn, Gwendolyn P; Ginsberg, Jill P; Loeffen, Erik A H; Hudson, Melissa M; Burns, Karen C; van Santen, Hanneke M; Berger, Claire; Diesch, Tamara; Dirksen, Uta; et al.
Summary: Patients with childhood, adolescent, and young adult cancer who will be treated with gonadotoxic therapies are at increased risk for infertility. Many patients and their families desire biological children but effective communication about treatment-related infertility risk and procedures for fertility preservation does not always happen. The PanCareLIFE Consortium and the International Late Effects of Childhood Cancer Guideline Harmonization Group reviewed the literature and developed a clinical practice guideline that provides recommendations for ongoing communication methods for fertility preservation for patients who were diagnosed with childhood, adolescent, and young adult cancer at age 25 years or younger and their families. Moreover, the guideline panel formulated considerations of the ethical implications that are associated with these procedures. Grading of Recommendations Assessment, Development and Evaluation methodology was used to grade the evidence and recommendations. In this clinical practice guideline, existing evidence and international expertise are combined to develop transparent recommendations that are easy to use to facilitate ongoing communication between health-care providers and patients with childhood, adolescent, and young adult cancer who might be at high risk for fertility impairment and their families.